2019
DOI: 10.1161/strokeaha.119.026373
|View full text |Cite
|
Sign up to set email alerts
|

Circulating DNAs, a Marker of Neutrophil Extracellular Traposis and Cancer-Related Stroke

Abstract: Background and Purpose— The role of circulating neutrophil extracellular traps (NETs) in cancer-related stroke is unknown. Methods— We conducted a prospective cohort study to test whether NETs are increased in cancer-related stroke and whether elevated NETs levels are associated with coagulopathy, assessed using D-dimer levels (≥2 μg/mL). Plasma DNA and nucleosome were assessed as NET-specific biomarkers. Results— … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 13 publications
2
34
0
1
Order By: Relevance
“…48 Our study and other studies showed that NETosis markers (e.g., circulating DNAs and citrullinated histone H2) were increased in patients with cancer-related stroke. 49,50 Increased circulating cancer cell-derived EVs could increase the formation of NETs in cancer-associated thrombosis. 49,51 Neutrophils, upon activation, release de-condensed chromatin for the formation of NETs, that promote thrombosis by the formation of a scaffold for adhesion of platelets, red blood cells, and platelet adhesion molecules such as fibrinogen, and activate both intrinsic and extrinsic coagulation pathways.…”
Section: Pathomechanisms Of Cancercoagulopathymentioning
confidence: 99%
“…48 Our study and other studies showed that NETosis markers (e.g., circulating DNAs and citrullinated histone H2) were increased in patients with cancer-related stroke. 49,50 Increased circulating cancer cell-derived EVs could increase the formation of NETs in cancer-associated thrombosis. 49,51 Neutrophils, upon activation, release de-condensed chromatin for the formation of NETs, that promote thrombosis by the formation of a scaffold for adhesion of platelets, red blood cells, and platelet adhesion molecules such as fibrinogen, and activate both intrinsic and extrinsic coagulation pathways.…”
Section: Pathomechanisms Of Cancercoagulopathymentioning
confidence: 99%
“…For example, the OASIS-Cancer study reported that patients with cancer and cryptogenic ischemic stroke have increased blood levels of extracellular vesicles and neutrophil extracellular trap formation (NETosis) than control patients. 14,15 Although both of these pathophysiological mechanisms are linked to hypercoagulability, their reproducibility and scalability may limit their clinical use. Furthermore, several studies have reported that plasma D-dimer levels are increased in patients with cancer and stroke, but D-dimer is a nonspecific fibrin degradation product and can be increased by stroke itself and in patients with cardiac disease.…”
mentioning
confidence: 99%
“…27 Cancer directly stimulates neutrophils to release decondensed chromatin, leading to the formation of neutrophil extracellular traps (NETs) that promote microthrombosis. 23,28 Thrombus in CRIS was also shown to be platelet-rich, which further confirmed that cancer cell may activate platelets, trigger thrombosis, and eventually lead to ischemic stroke. 29,30 The present study showed that BCRIS patients had significantly higher platelets counts and triggered thrombosis by increased platelets, which played a role in BCRIS occurrence.…”
Section: Discussionmentioning
confidence: 67%
“…Several animal studies showed that cancer cells can release extracellular vesicles into the circulating blood, leading to an increase in D-dimer levels and further triggering the development of microthrombosis, which suggests that cancer could lead to CRIS through the hypercoagulability pathway. 15,23 Previous studies showed that elevated serum D-dimer levels were associated with hypercoagulability and CRIS. 5,24 Seok et al 24 reported that the elevated Ddimer level was linearly correlated with the increase in microthrombus signals that were detected by superior and Doppler ultrasound of the internal carotid artery in stroke patients with active cancer; this further confirmed the association between hypercoagulability and CRIS.…”
Section: Discussionmentioning
confidence: 99%